Reconstruction or Creation? The Liberation of a Concentration Camp in Andrzej Wajda's Landscape After Battle - Tomasz Łysak (Slovo, 2013)
Andrzej Wajda's images of spontaneous exuberance captured in the opening scene of (1970) are used to gauge the realism of his cinematic vision of the liberation. The essay focuses on: reception, critical reviews concerning fidelity to Tadeusz Borowski's short stories, and filmmaker's declarations in 1969 and two decades later. Other reference materials entail memoirs of American liberators and photographic record of the liberation of Dachau and its sub-camp Dachau Allach. Wajda has refused to reproduce the actual camp because the horror was unattainable for the crew. Thus, the film should be placed in the realm of creation rather than meticulous reconstruction. Click here to read the article